Denotasi Dan Konotasi Jenis Simbol Dalam Film Animasi “Le Magasin Des Suicides”: Pendekatan Semiotika Teori Barthes - Andina Noviyanti Putri; Yuliarti Mutiarsih; Rika Widawati (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
Animated films serve not only as entertainment but also as a medium for conveying social criticism through symbolic representation. This study aims to examine the denotative and connotative meanings of verbal and nonverbal symbols in the animated film Le Magasin des Suicides using Barthes semiotic approach. A descriptive qualitative method was employed, with observation and note-taking techniques to identify scenes containing symbolic representations of death. Data were selected purposively from key scenes that illustrate death-related symbolism and analyzed through Barthes theory of signs. The findings reveal that symbols such as hanging ropes, poison, knife, promotional slogans, and coffin-shaped birthday cakes not only carry literal meanings but also convey ideological critiques related to nihilism, consumerism, and the commodification of death in modern society. The film reflects how death is normalized and commodified within daily routines through dark humor. Thus, this animated film functions not merely as entertainment but as a form of social commentary, revealing how modern culture constructs and interprets the concept of death.